Hysteroscopic surgery for treating intramural fibroids at the cesarean scar area: a case report and literature review - Wu, Juntong; Liu, Yuan; Zhang, Lili; Ma, Dongji; Yao, Tianming; Wang, Li (Frontiers in Medicine, 2025)
BackgroundUterine fibroids located at cesarean section scar sites are rare and differ clinically from conventional fibroids, frequently causing abnormal uterine bleeding and infertility. Traditional surgical approaches (laparotomy, laparoscopy, or vaginal surgery) necessitate incision of the scar site, resulting in significant tissue damage. We present a successful case of hysteroscopic resection for such fibroids, demonstrating the minimally invasive advantages of this approach.Case summaryA 49-year-old multiparous woman with a history of cesarean delivery presented with a 2-year history of menorrhagia and prolonged menstrual cycles, exacerbated over the preceding month. Gynecological ultrasound revealed heterogeneous hypoechogenicity within the cervical canal, measuring approximately 5.3 cm × 3.5 cm × 3.3 cm in size. The physical examination revealed an enlarged uterus, approximately the size of 11 cm × 8 cm × 7 cm. Hematologic workup showed the hemoglobin (HGB) level of 65 g/L. Based on these examination results, a clinical diagnosis of “uterine fibroids, secondary anemia” was conducted. Hysteroscopy examination showed that the base of the uterine fibroid was attached to the scar site of the original cesarean section, without a pedicle, and the main body of the fibroid remained in the cervical canal—intraoperative definitive diagnosis: intramural fibroids at the scar site of the uterus. Therefore, a hysteroscopic approach with a bipolar resectoscope was used to remove the intramural fibroids in the scar area of the uterus. The procedure consumed 22,000 ml of fluid distension media (0.9% NaCl) and lasted for 1 h and 45 min. The postoperative pathological diagnosis was uterine leiomyoma, consistent with the preoperative diagnosis. A follow-up was conducted 3 months after surgery, and a gynecological ultrasound examination showed complete removal of uterine fibroids.ConclusionThis case confirmed that hysteroscopic resection of cesarean scar intramural fibroids is a feasible, safe, and minimally invasive approach.